Cardiac Findings in Amyotrophic Lateral Sclerosis: A Magnetic Resonance Imaging Study - Rosenbohm, Angela; Schmid, Benjamin; Buckert, Dominik; Rottbauer, Wolfgang; Kassubek, Jan; Ludolph, Albert C.; Bernhardt, Peter (Frontiers in Neurology, 2017)
The objective of this study was to investigate the potential involvement of cardiac structure and function by cardiac magnetic resonance (CMR) imaging in amyotrophic lateral sclerosis (ALS) patients. Our study included 35 patients with ALS without a history of cardiac disease and an age and gender matched healthy control group (n=34). All subjects received a CMR in a 1.5T whole-body scanner. Patients were also screened with Holter monitoring, echocardiography and a blood test of cardiac markers. Myocardial mass in ALS hearts were reduced compared to the control group, and ejection volumes in the left and right heart were severely decreased in ALS patients, as shown by echocardiography and CMR. The myocardium showed increased T1 enhancement in 77% of the patients compared to 27% of controls (p=0.0001). A trend towards late gadolinium enhancement patterns consistent with myocardial fibrosis was observed in 23.5% of the patients (9.1% of controls). Holter monitoring was normal in all patients as well as troponin T. Cardiac involvement seems to be present in ALS patients without clinical cardiac symptoms and with a normal cardiac routine assessment. Structural myocardial defects in CMR may be due to sympathetic dysfunction and may account for reported cardiac deaths in late-stage ALS patients.